Analysis of death in children not submitted to cardiopulmonary resuscitation - Márcia Marques Leite; Fernanda Paixão Silveira Bello; Tânia Miyuki Shimoda Sakano; Claudio Schvartsman; Amélia Gorete Afonso da Costa Reis (Elsevier, 2022)
Objective: Describe the epidemiology of deaths in children not submitted to CPR, compare to a CPR group and evaluate patients' medical records of those not submitted to CPR. Methods: Observational cross-sectional study assessing deaths between 2015 and 2018 in a pediatric tertiary hospital, divided into two groups: CPR and no- CPR. The source of data included the cardiorespiratory arrest register, based on Utstein style. Children's medical records in no-CPR group were researched by hand. Results: 241 deaths were included, 162 in CPR group and 79 in the no-CPR group. Preexisting diseases were observed in 98.3% of patients and prior advanced intervention in 78%. Of the 241 deaths, 212 (88%) occurred in the PICU, being 138/162 (85.2%) in CPR group and 74/79 (93.7%) in no-CPR group (p = 0.018). Bradycardia as the initial rhythm was five times more frequent in the CPR group (OR 5.06, 95% CI 1.94-13,19). There was no statistically significant difference regarding age, gender, preexisting diseases, and period of the day of the occurrence of death. Medical records revealed factors related to the family decision-making process or the suitability of therapeutic effort. Discrepancies between the practice of CPR and medical records were identified in 9/79 (11,4%) records allocated to the no-CPR group. Conclusion: Most deaths with CPR and with the no-CPR occurred in the PICU. Bradycardia as the initial rhythm was five times more frequent in the CPR group. Medical records reflected the complexity of the decision not to perform CPR. Discrepancies were identified between practice and medical records in the no-CPR group.